The Impact of Frailty on Technique Failure and Mortality in Patients on Home Dialysis. Issue 6 (November 2019) - Brar, Ranveer; Whitlock, Reid; Komenda, Paul; Lerner, Blake; Prasad, Bhanu; Bohm, Clara; Thorsteinsdottir, Bjoerg; Rigatto, Claudio; Tangri, Navdeep
Background: Patients on home dialysis therapies experience technique failure, which is associated with morbidity and mortality. Reasons for technique failure are complex, and often related to functional decline in the patient or caregiver. Frailty is associated with an increased risk of adverse health outcomes. We investigated the impact of frailty on technique failure and mortality in a prospective cohort of patients on home dialysis therapies. Methods: We collected objective (Fried criteria and Short Physical Performance Battery [SPPB]), and subjective (physician and nurse impression) measures of frailty from 109 prevalent home dialysis patients. Our primary outcome was a composite of technique failure, defined as a permanent unplanned transition (> 30 days in duration) to facility-based hemodialysis or all-cause death. The association between different frailty assessment tools and the primary composite outcome was evaluated using Cox models. Results: Fried criteria and physician impression was associated with a greater than 2-fold increase in risk of our composite outcome (HR: 2.10 [95% CI 1.09 – 3.99], 2.15 [95% CI 1.15 – 4.00, respectively] in adjusted analyses. Weakness and weight loss subdomains of the Fried criteria were both associated with an increased risk of our composite outcome in adjusted analyses (HR: 2.16 [95% CI 1.23 – 3.78], 2.69 [95% CI 1.39 – 5.40], respectively). Conclusions: Objective and subjective measures of frailty are associated with a more than 2-fold higher risk of technique failure or death in patients undergoing home dialysis. Assessing frailty as part of the clinical evaluation for home dialysis therapies may be useful for prognostication and clinical management.